Analisis perbandingan pengaruh store atmosphere terhadap loyalitas pelanggan coffee shop di Bandung - Christian Bernard Gunawan; Syahputra Syahputra (Universitas Kristen Maranatha, 2020)
Nowadays, increasing in the Indonesia coffee industry, especially in Bandung city, is more interesting to be researched more deeply. This research was conducted to determine store atmosphere and customer loyalty at coffee shops in Bandung city, how much impact it has, also there is a difference in customer loyalty at coffee shops in Bandung city. In this research, researchers use a quantitative method, with the type of research is descriptive-causality. Sampling was used non-probability method, with purposive sampling type, by 20 respondents in each of the five coffee shops. By using descriptive analysis, simple regression analysis, and one-way ANOVA methods, the results show that store atmospheres significantly affect customer loyalty at coffee shops. Besides that, this research found that store atmospheres have an effect of 38,8% on customer loyalty and other factors that do not in this research effect of 61,2%. This research also shows that there is no difference in customer loyalty at coffee shops. Researchers concluded that store atmosphere and customer loyalty at these five coffee shops in Bandung, already included in the excellent category. However, these five coffee shops need to lead a different uniqueness from the side of store atmospheres. This matter is necessary, so customers feel a different store atmosphere from others, thus becomes the uniqueness of coffee shops. This research expects to provide input for five coffee shops that researched and coffee shop entrepreneurs, as well as being information for further study.